2009
DOI: 10.1523/jneurosci.6012-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Internalization by Sensory Neurons Is Megalin Mediated and Necessary for Its Neuritogenic Activity

Abstract: Mutated transthyretin (TTR) causes familial amyloid polyneuropathy, a neurodegenerative disorder characterized by TTR deposition in the peripheral nervous system (PNS). The origin/reason for TTR deposition in the nerve is unknown. Here we demonstrate that both endogenous mouse TTR and TTR injected intravenously have access to the mouse sciatic nerve. We previously determined that in the absence of TTR, both neurite outgrowth in vitro and nerve regeneration in vivo were impaired. Reinforcing this finding, we no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 49 publications
4
89
0
Order By: Relevance
“…Recently, megalin-TTR interaction was also described in sensory neurons where TTR effect in neurite outgrowth and nerve regeneration was shown to be mediated by megalindependent internalization, further supporting the relevance of this interaction (35).…”
Section: Megalin: the Receptor For Renal Uptake Of Ttrmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, megalin-TTR interaction was also described in sensory neurons where TTR effect in neurite outgrowth and nerve regeneration was shown to be mediated by megalindependent internalization, further supporting the relevance of this interaction (35).…”
Section: Megalin: the Receptor For Renal Uptake Of Ttrmentioning
confidence: 73%
“…Although no further study described the impact of TTR-MT interaction, more common features of the proteins were identified. TTR has neuritogenic activity dependent on megalin-mediated internalization (35). Interestingly, MT stimulation of neurite outgrowth is also mediated by megalin (47).…”
Section: The Common Features In the Biology Of Metallothionein 2 (Mt2mentioning
confidence: 99%
“…Membrane associated proteins of 90, 100, and 115 kDa have earlier been proposed as receptor proteins involved in endocytosis of TTR, although they have not been identified [8][9][10]15]. Megalin is a member of the low-density lipoprotein receptor family [16] and it has been shown to be involved in renal and sensory neuronal uptake of TTR [17,18]. Megalin is an endocytotic receptor expressed in clathrin-coated pits and binds the receptor-associated protein (RAP) which functions as a chaperone.…”
Section: Discussionmentioning
confidence: 99%
“…24 Fibroblasts, together with macrophages, also have a central role in degrading and remodelling the ECM. Although, different types of cells reportedly exhibit varying degrees of TTR internalization activity in vitro, [13][14][15] fibroblasts and macrophages have higher migratory potential and more accessibility to TTR deposits in ECM. Previous ultrastructural analyses revealed amyloid deposits at the outer layer of the basement membrane, which occurs at the base of all epithelial linings, underlying endothelia of capillaries and venules, and around Schwann cells, adipocytes, and muscle cells.…”
Section: Role Of Fibroblasts In Ttr Amyloidosismentioning
confidence: 99%
“…12 Previous in vitro studies showed that WT and mutant TTR are internalized by different types of cells, including hepatocytes, mouse embryonic fibroblasts, yolk sac cells, and sensory neurons. [13][14][15] Whether these cells could endocytose and degrade TTR aggregates in vivo needs investigation.…”
mentioning
confidence: 99%